(untitled) (Research, Society and Development, 2020)
This paper presents the proposal of Money Identifier, an application for use on mobile devices (tablets and smartphones), which aims to provide accessibility for people with visual impairment or reduced vision, as well as people with difficulty identifying and adding money. The application came from a blind student needs, and the student performed the validation of the app interface. This paper presents here its interface and the possibilities offered by the application to the user.